Comparative pathogenicity of BA.2.12, BA.5.2 and XBB.1 with the Delta variant in Syrian hamsters - Mohandas, Sreelekshmy; Shete, Anita; Kumar, Abhimanyu; Wakchaure, Kundan; Rai, Vishal; Mote, Chandrasekhar; Dighe, Hitesh; Sarkale, Prasad; Gawande, Pranita; Yemul, Jyoti; Suryawanshi, Annasaheb; Joshi, Yash; et al. (Frontiers in Microbiology, 2023)
Omicron variant is evolving into numerous sub variants with time and the information on the characteristics of these newly evolving variants are scant. Here we performed a pathogenicity evaluation of Omicron sub variants BA.2.12, BA.5.2 and XBB.1 against the Delta variant in 6–8-week-old Syrian hamster model. Body weight change, viral load in respiratory organs by real time RT-PCR/titration, cytokine mRNA quantification and histopathological evaluation of the lungs were performed. The intranasal infection of the BA.2.12, BA.5.2 and XBB.1 variants in hamster model resulted in body weight loss/reduced weight gain, inflammatory cytokine response and interstitial pneumonia with lesser severity compared to the Delta variant infection. Among the variants studied, BA.2.12 and XBB.1 showed lesser viral shedding through the upper respiratory tract, whereas the BA.5.2 showed comparable viral RNA shedding as that of the Delta variant. The study shows that the Omicron BA.2 sub variants may show difference in disease severity and transmissibility amongst each other whereas the overall disease severity of the Omicron sub variants studied were less compared to the Delta variant. The evolving Omicron sub variants and recombinants should be monitored for their properties.